Convenient preparation of pinometostat and related 5′-deoxy-5′-amino adenosine derivatives as well as their activity against DOT1L. Issue 4 (24th January 2018) - Liu, Tongchao; Ren, Huanming; Li, Cong; Chen, Guohua; Cheng, Maosheng; Zhao, Dongmei; Shen, Jingkang; Li, Jia; Zhou, Yubo; Xiong, Bing; Chen, Yue-Lei
Graphical abstract: Highlights: Pinometostat was made in 3 steps from adenosine in 47% yield. Six other nucleoside DOT1L inhibitors were made efficiently, too. 2′- C -Me Nucleoside DOT1L inhibitors were evaluated for the enzyme activities. Rapid access to various 5′-deoxy-5′-amino adenosine derivatives. Abstract: From adenosine and 2′- C -Me adenosine, a 3-step route towards nucleoside DOT1L inhibitors, including pinometostat, EPZ5677, and FED1, was established. With useful structural-activity relationship information, the newly prepared 2′- C -Me adenosine derivatives contribute to the limited repertoire of ribose-modified nucleoside DOT1L inhibitors. In general, this new synthetic method will facilitate not only the study of nucleoside DOT1L inhibitors, but also the synthetic and medicinal chemistry research of 5′-deoxy-5′-amino adenosine derivatives.